2022
DOI: 10.1177/15407969221126496
|View full text |Cite
|
Sign up to set email alerts
|

Ecobehavioral Analysis of the Experiences of Students With Complex Support Needs in Different Classroom Types

Abstract: Students with complex support needs frequently experience restrictive educational placements such as self-contained and separate school classrooms. Given the need to support students with complex support needs to experience positive outcomes and make progress in the general education curriculum, there is a need to investigate the characteristics of the classroom contexts in which they are learning. The purpose of this study was to use ecobehavioral assessment observation methods to investigate how student beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For example, the authors found that in resource, self-contained, and separate school classrooms educators were significantly more likely to be focused on other adults, rather than being focused on students, when compared to educators in general education classrooms. Further, educators in self-contained and separate school classrooms were significantly more likely to be providing no instruction to students, compared to educators in general education classrooms (Zagona et al, 2022). Gee et al (2020) analyzed the instructional progress and outcomes of 15 pairs of students with ESN in one district who were matched on 12 characteristics (e.g., disability labels, eligibility for alternate assessment, communication, literacy, and numeracy levels) by comparing their first and most recent individualized education programs (IEPs).…”
Section: Macrosystems Of Education Team Membersmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, the authors found that in resource, self-contained, and separate school classrooms educators were significantly more likely to be focused on other adults, rather than being focused on students, when compared to educators in general education classrooms. Further, educators in self-contained and separate school classrooms were significantly more likely to be providing no instruction to students, compared to educators in general education classrooms (Zagona et al, 2022). Gee et al (2020) analyzed the instructional progress and outcomes of 15 pairs of students with ESN in one district who were matched on 12 characteristics (e.g., disability labels, eligibility for alternate assessment, communication, literacy, and numeracy levels) by comparing their first and most recent individualized education programs (IEPs).…”
Section: Macrosystems Of Education Team Membersmentioning
confidence: 94%
“…For instance, Mayton et al (2014) found that many district personnel assume that students with ESN can only receive individualized instruction in segregated environments. During observations of 116 students with ESN across the United States, Zagona et al (2022) did not find evidence of practices meant to address students' needs (e.g., greater access to individualized supports) that commonly are used as a rationale for maintaining a student with disabilities in segregated placements. For example, the authors found that in resource, self-contained, and separate school classrooms educators were significantly more likely to be focused on other adults, rather than being focused on students, when compared to educators in general education classrooms.…”
Section: Macrosystems Of Education Team Membersmentioning
confidence: 98%
“…The mere physical integration of autistic children in mainstream classrooms is widely considered insufficient for a successful educational experience (25,48), but that does not mean that the solution is to place them in a segregated placement. It must move toward ensuring students with ASD are served in inclusive, general education classrooms, where they can access academic instruction, meaningful interactions and relationships with peers, and supplementary aids and services (49)(50)(51).…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%
“…SETs, particularly those that work with students with extensive learning, behavioral, and social-emotional needs (often in a more restricted self-contained setting), spend a disproportionate amount of their time with out-of-classroom demands (Zagona et al, 2022). Kurth and colleagues (2016) reported that these SETs spend up to 47% of their time engaged in non-teaching tasks and are two to three times more likely to be focused on non-teaching tasks during instructional time than teachers in general education settings (Zagona et al, 2022). These non-teaching and non-student-facing responsibilities include IEP management (e.g., writing present levels, collaborating with team members, progress monitoring, and updating progress), parent communication, and lesson planning.…”
mentioning
confidence: 99%